2023
DOI: 10.1302/0301-620x.105b9.bjj-2023-0238.r1
|View full text |Cite
|
Sign up to set email alerts
|

Anterosuperior versus deltopectoral approach for primary reverse total shoulder arthroplasty

Arno A. Macken,
Arnela Haagmans-Suman,
Anneke Spekenbrink-Spooren
et al.

Abstract: AimsThe current evidence comparing the two most common approaches for reverse total shoulder arthroplasty (rTSA), the deltopectoral and anterosuperior approach, is limited. This study aims to compare the rate of loosening, instability, and implant survival between the two approaches for rTSA using data from the Dutch National Arthroplasty Registry with a minimum follow-up of five years.MethodsAll patients in the registry who underwent a primary rTSA between January 2014 and December 2016 using an anterosuperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The difference in follow-up time may be a source of bias, however, a previous study found no significant changes in results after 1 year, which was the minimum follow-up in this study [8]. Furthermore, the approach differed between the groups (the anterosuperior approach was used for regular RSA and the deltopectoral approach for BIO-RSA); however, the approach did not influence outcomes in previous studies [40,41]. Second, bone graft healing and viability, and implant positioning is best assessed on computed tomography (CT) scans instead of radiographs.…”
Section: Limitationsmentioning
confidence: 52%
“…The difference in follow-up time may be a source of bias, however, a previous study found no significant changes in results after 1 year, which was the minimum follow-up in this study [8]. Furthermore, the approach differed between the groups (the anterosuperior approach was used for regular RSA and the deltopectoral approach for BIO-RSA); however, the approach did not influence outcomes in previous studies [40,41]. Second, bone graft healing and viability, and implant positioning is best assessed on computed tomography (CT) scans instead of radiographs.…”
Section: Limitationsmentioning
confidence: 52%
“…This study from various centres, including Annecy (France) , compared the outcomes of these approaches using data from the Dutch National Arthroplasty Registry. 6 This is an important study as, to date, very little has been reported on any potential differences, and with a minimum follow-up of five years there is enough clinical follow-up here to identify any medium-term differences in outcomes. The aim was to assess the rate of complications, including glenoid loosening, instability, and overall implant survival between surgery undertaken with these two different approaches.…”
Section: Anterosuperior Versus Deltopectoral Approach For Primary Rev...mentioning
confidence: 96%